Critical Care Update 2021 - Govil, D. Deepak; Dixit , S. B. Subhal Bhalchandra; Chaudhry, D. Dhruva; Todi, S. Subhash (Jaypee Brothers Medical Publishers, 2022)
The objective and endeavor of the book remain to enhance knowledge and strengthen clinical practice in critical care. The book broadly covers depths of scientific topics over all major organ systems and global current critical care practices. It is styled to serve as a ready bedside reference guide to all practitioners of critical care medicine. This book comprised of 14 section that focus on respiratory system, extracorporeal life support system, hemodynamics, cardiovascular, sepsis and septic shock, nutrition, gastroenterology, USG and ECHO, renal and electrolytes, neurocritical care, Covid related ICU issues, etc. The ratio of chapter distribution is in keeping with the relative scientific work done in the respective field. ISCCM has allocated a substantial space to the Quality, Research and Organizational aspect keeping in mind the growing importance of these often neglected areas of critical care. The topics have been carefully selected by the ISCCM National Scientific Committee and the contributors are mostly national and international faculty in the congress.